PELATIHAN BUDIDAYA SAYURAN ORGANIK DI DESA DARU KECAMATAN KAO UTARA - Ariance Yeane Kastanja; Zeth Patty; Zakarias Dilago (LPPM Universitas Abdurrab, 2019)
This community empowerment activity is carried out to improve the skills and abilities of women's farmer groups, especially in the cultivation of organik vegetables, making liquid organik fertilizer, and making fruit fly traps. The low level of knowledge and skills in cultivating organik vegetables is a problem faced by women's farmer groups. The method used in this activity is in the form of counseling, training and making organik vegetable demonstration plots. The activities carried out are divided into several stages, including the initial meeting with the group, submission of tools and supporting materials for cultivation activities, preparation of extension and training tools and materials, extension of organik vegetable cultivation, pest and disease counseling, training on making fruit fly traps and training in making organik fertilizers as well as making vegetable plant demonstration plots. The results of this activity are improving the ability and skills of producing liquid organik fertilizer, making fly traps, and cultivating organik vegetables.